Forestry development prospects in the Imatong Central Forest Reserve, Southern Sudan: volume 2 (main report) - Jenkin, R; Howard, W; Thomas, P; Abell, T; Deane, G (Land Resources Division, Ministry of Overseas Development, 1977)
An area of nearly 10000 ha has been demarcated in the Ngairigi and Upper Kinyeti Basins for the development of softwood plantations. Some 6 000 ha of the area selected has been designated Class 1 land, having no or only minor limitations for plantation development. An enumeration of 490.8 ha of existing plantations has revealed a standing volume of 127 000 m3. Recommendations are made for clear felling 274.8 ha, which can be expected to yield about 84 900 m3, for thinning 152.2 ha, which would yield about 9 800 m3, for pruning 99.4 ha and for weeding, cleaning and beating up 60.0 ha. Of the area selected for plantation development, 6405.6 ha are covered by vegetation types containing merchantable timber species. These types include Croton - Macaranga - Albizia forest, Olea - Podocarpus closed forest, Podocarpus - Syzygium open forest and Podocarpus - Dombeya open forest and together they contain about 841 500 m3 of timber of which 186000 m3 is Podocarpus and 203600 m3 is established hardwoods. An enumeration of the Talanga forest showed that there was a standing volume of about 258500 m3 over some 2 135.7 ha, and this would keep the Katire sawmill supplied with timber for between 5 and 11 years, depending upon the area over which it proved possible to extract economically.